Gamification in Learning : Students’ Motivation and Cognitive Engagement in Learning Business Using Quizizz - Zainun Amirah, Zainudin; Norehan, Zulkiply (AJUE, 2023)
Gamification has received extensive research attention within the context of language and scientific courses, involving the integration of game-based features into non-gaming scenarios to enhance user experience and engagement with technology. However, contradictory findings have emerged in students' perceptions of gamification across various aspects such as motivation and engagement, as noted in previous studies. Given the conflicting findings from prior research on students' perception toward gamification in learning, a need for further investigation becomes evident. Recognising the significance of broadening gamification exploration beyond language and science oriented courses, this study aims to examine students' perceptions of gamification in learning. Additionally, it seeks to evaluate students' levels of motivation and cognitive engagement while studying Business using the Quizizz platform. To achieve these objectives, a mixed-method approach was employed. Data collection was conducted through online questionnaires and interviews. The quantitative data from the questionnaires underwent descriptive analysis, while the qualitative data gathered from online interviews were subjected to narrative analysis. The findings of the study suggest that students demonstrate a high level of motivation and cognitive engagement when employing Quizizz for Business studies. Participants expressed favourable opinions of Quizizz due to its interactive gamification components. Importantly, elements like points, rewards, leaderboards, and varying levels of difficulty within Quizizz emerged as crucial factors influencing students' motivation and cognitive engagement in the context of Business learning.